Analisis pengaruh Strategi Pemasaran terhadap Kinerja Usaha melalui Kemampuan Pemasaran pada UMKM Tenun di Kota Bima: Pendekatan Technology Acceptance Model (TAM) - Muhajirin, Muhajirin; Sanaji, Sanaji; Andjarwati, Anik Lestari (Universitas Riau Kepulauan, 2025)
Abstract This study aims to analyze the influence of Marketing Strategy on Business Performance through Marketing Capability in Weaving SMEs in Bima City: A Technology Acceptance Model (TAM) Approach. Amid the significant potential of weaving SMEs in both local and global markets, challenges in the adoption of digital technology remain a major obstacle. This research adopts a quantitative approach using a survey method involving 100 weaving SME actors selected through purposive sampling. Data analysis was conducted using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method. The results indicate that marketing strategy has a significant effect on both marketing capability and business performance. Furthermore, marketing capability is proven to mediate and strengthen the relationship between marketing strategy and business performance. These findings underscore the importance of enhancing digital-based marketing capabilities as a fundamental pillar in improving the performance and competitiveness of weaving SMEs in the digital transformation era. The practical implications of this study encourage synergy among business actors, government, and supporting institutions to accelerate inclusive and sustainable digital technology adoption in the SME sector based on local wisdom.